Reproductive phenology of Ditassa burchellii (Apocynaceae, Asclepiadoideae), a herbaceous vine, in a semi-deciduous forest from Brazil - Fontes,Anderson Lopes (2019)
Abstract We analyzed the reproductive phenology of Ditassa burchellii and the influence of abiotic factors on the species phenophases. The study was conducted on individuals of a natural population from a semi-deciduous forest (Viçosa municipality, Minas Gerais state, southeastern Brazil). We quantified the activity and intensity indices of the following phenophases: flower bud, flower, immature fruit, and dehiscent fruit. To test for seasonality of phenophases, we analyzed each of them using Rayleigh test. We evaluated whether there was any association between abiotic variables (mean temperature, rainfall, and day length) and phenophases, in the month of occurrence and in the three months prior to the occurrence of each phenophase. The analyzed phenophases occurred mainly at the end of the rainy season and during the dry season, with overlapping periods, but with sequential peaks. The periods of occurrence of reproductive phenophases were similar to the ones in other climbing species and were mainly related to the dispersal mode. All phenophases were seasonal and were associated with at least one abiotic variable, either in the month of their occurrence or in the previous months.